Thin films of copper antimony sulfide: A photovoltaic absorber material. (January 2015) - Ornelas-Acosta, R.E.; Shaji, S.; Avellaneda, D.; Castillo, G.A.; Das Roy, T.K.; Krishnan, B.
Graphical abstract: Highlights: CuSbS2 thin films were prepared by heating Sb2 S3 /Cu layers. Analyzed the structure, composition, optical, and electrical properties. PV structures: glass/SnO2 :F/ n -CdS/ p -CuSbS2 /C/Ag were formed at different conditions. The PV parameters ( J sc, V oc, and FF) were evaluated from the J – V characteristics. J sc : 0.52–3.20 mA/cm 2, V oc :187–323 mV, FF: 0.27–0.48 were obtained. Abstract: In this work, we report preparation and characterization of CuSbS2 thin films by heating glass/Sb2 S3 /Cu layers and their use as absorber material in photovoltaic structures: glass/SnO2 :F/ n -CdS/ p -CuSbS2 /C/Ag. The Sb2 S3 thin films of 600 nm were prepared by chemical bath deposition on which copper thin films of 50 nm were thermally evaporated, and the glass/Sb2 S3 /Cu multilayers were heated in vacuum at different temperatures. X-ray diffraction analysis showed the formation of orthorhombic CuSbS2 after heating the precursor layers. Studies on identification and chemical state of the elements were done using X-ray photoelectron spectroscopy. The optical band gap of the CuSbS2 thin films was 1.55 eV and the thin films were photoconductive. The photovoltaic parameters of the devices using CuSbS2 as absorber and CdS as window layer were evaluated from the J – V curves, yielding J sc, V oc, and FF values in the range of 0.52–3.20 mA/cm 2, 187–323 mV, and 0.27–0.48, respectively, under illumination of AM1.5 radiation.